Multicriterial analysis in the decision-making aid: Case study in the São Gonçalo reservoir, Paraíba, Brazil - Santos, Valterlin da Silva; Nobrega, Aila Katamara Queiroga (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The São Gonçalo reservoir, located in the municipality of Sousa, Paraíba, collapsed in August 2015, so that the populations of the cities supplied by the reservoir suffered from a rationing of water and the agricultural activity in São Gonçalo Irrigated Perimeter and in the areas around the reservoir were suspended. Therefore, the aim of this article is evaluate the best mode of operating the reservoir water resources so that this fact not occurs again. Thus, it was proposed five (5) alternatives of operating considering the main uses and water levels of reservoir. The multicriteria analysis method Prometheee II was used to find the best alternative. The were established evaluate criteria in two dimensions (criteria for the use of water in the reservoir and criteria for the use of water by irrigated agriculture). The subjectivity human decision was analyzed through 11 (eleven) possible weight scenarios for each dimension. The results indicated that alternative 3 (suspension of irrigation when the reservoir level is below 20% of the storage capacity) and alternative 4 (decrease of water intended for irrigation when the reservoir level reaches 40% of the storage capacity and suspension of the irrigation activity when the reservoir level is below 20% of the storage capacity) are the best alternatives for reservoir operation depending on the weight intended for each dimension, but this alternatives may also be the worst.